The deubiquitylating enzyme Fat facets promotes Fat signalling and restricts tissue growth. - Dawson, L.E.; Sekar, A.; Fulford, A.D.; Lambert, R.I.; Burgess, H.S.; Ribeiro, P.S. (Nature communications, 2025)
Tissue growth is regulated by many signals, including polarity cues. The Hippo signalling pathway restricts tissue growth and receives inputs from the planar cell polarity-controlling Fat signalling pathway. The atypical cadherin Fat restricts growth via several mechanisms that ultimately control the activity of the pro-growth transcriptional co-activator Yorkie. Fat signalling activates the Yorkie inhibitory kinase Warts, and modulates the function of the FERM protein Expanded, which promotes Hippo signalling and also directly inhibits Yorkie. Although several Fat pathway activity modulators are known to be involved in ubiquitylation, the role of this post-translational modification in the pathway remains unclear. Moreover, no deubiquitylating enzymes have been described in this pathway. Here, using in vivo RNAi screening, we identify the deubiquitylating enzyme Fat facets as a positive regulator of Fat signalling with roles in tissue growth control. Fat facets interacts genetically and physically with Fat signalling components and regulates Yorkie target gene expression. Thus, we uncover a role for reversible ubiquitylation in the control of Fat signalling and tissue growth regulation.